Genetic analysis of physiological components of salt tolerance conferred by Solanum rootstocks. What is the rootstock doing for the scion? - Asins, María J.; Bolarin, M. C.; Pérez-Alfocea, Francisco; Estan, M. T.; Martínez-Andújar, Cristina; Albacete, Alfonso; Villalta, Irene; Bernet, Guillermo P.; Dodd, Ian C.; Carbonell, Emilio A. (2017)
Grafting desirable crop varieties on stress-tolerant rootstocks provides an opportunity to increase crop salt tolerance. Here, a commercial hybrid tomato variety was grafted on two populations of recombinant inbred lines developed from a salt-sensitive genotype of Solanum lycopersicum var. cerasiforme, as female parent, and two salt-tolerant lines, as male parents, from S. pimpinellifolium, the P population, and S. cheesmaniae, the C population, to identify an easy screening method for identifying rootstocks conferring salt tolerance in terms of fruit yield. Potential physiological components of salt tolerance were assessed in the scion: leaf biomass, [Na(+)], nutrition, water relations and xylem ABA concentration. A significant correlation between scion fruit yield and scion leaf fresh weight, water potential or the ABA concentration was found in the C population under salinity, but the only detected QTL did not support this relationship. The rootstocks of the P population clearly affected seven traits related to the sodium, phosphorous and copper concentrations and water content of the scion leaf, showing heritability estimates around 0.4 or higher. According to heritability estimates in the P population, up to five QTLs were detected per trait. QTLs contributing over 15% to the total variance were found for P and Cu concentrations and water content of the scion leaf, and the proportion of fresh root weight. Correlation and QTL analysis suggests that rootstock-mediated improvement of fruit yield in the P population under salinity is mainly explained by the rootstock's ability to minimise perturbations in scion water status.